2014
DOI: 10.11604/pamj.2014.19.392.4242
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of detection methods for Campylobacter infections among under-fives in Mwanza City, Tanzania

Abstract: IntroductionCampylobacter species are recognized as a major cause of acute gastroenteritis in humans throughout the world. The diagnosis is mainly based on stool culture. This study was done to evaluate the effectiveness of staining methods (Gram stain using 0.3% carbol fuchsin as counter stain and 1% carbol fuchsin direct stain) versus culture as the gold standard.MethodsA total of 300 children attending Bugando Medical Centre (BMC) and the Sekou Toure regional hospital with acute watery diarrhea were enrolle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…To overcome this limitation, microscopists should regularly be re-trained and tested. In accordance with other reports, the specificity of Campylobacter staining in our study was high [14, 2024]. Positive results therefore, provide rapid and clinically relevant information.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…To overcome this limitation, microscopists should regularly be re-trained and tested. In accordance with other reports, the specificity of Campylobacter staining in our study was high [14, 2024]. Positive results therefore, provide rapid and clinically relevant information.…”
Section: Discussionsupporting
confidence: 92%
“…In a previous study using the same technique in Chile, the sensitivity was higher, but the difference was not statistically significant (37.5 %, CI95 % 16.3–64.1) [14]. Other studies using different stains such as Gram, reported much higher sensitivity values from 44 to 94 % [2024]. Reasons for the lower sensitivity in our study might be the use of a different staining technique, diagnostic settings (study versus routine conditions), study populations (children versus adults), and technical problems with Campylobacter culture, especially in older reports or in studies from developing countries.…”
Section: Discussionmentioning
confidence: 91%
“…But higher prevalence of Campylobacter species were detected in diarrhoeic children 21%. 21 and 47.4%, 23 in Malawi and South Africa respectively; whereas lower prevalence of 2% in Sudan, 24 4.7% in Tanzania, 25 and 7.0% in Kolkata, India. 26…”
Section: Discussionmentioning
confidence: 90%